Advancements and new technologies in drug delivery system - Sahi A.K.; Verma P.; Pallawi; Singh K.; Mahto S.K. (My University, 2025)
Drug delivery is defined as administration of drug component inside the body, and the system adopted for the same is known as drug delivery system. Advancements in the drug delivery system are gaining more attention and popularity due to the use of nanoformulations that enables efficient, effective and specific targeting of the drug. Several drug carriers such as liposomes, aptamers, quantum dots, peptide, polymers, metals and magnetic nanoparticlebased delivery are categorised as advanced generation drug delivery systems. The structural complexity of nano-based drug delivery system, e.g. nanocapsules, dendrimers, nanosponges, nanocrystals, nanogels and nanocapsules, provides high surface area for precise targeting in the field of cancer management and several other life-threatening diseases. © Springer Nature Singapore Pte Ltd. 2019.